Formulation of Bergamot Essential Oil-Loaded Emulsion for Hyperhidrosis and Bromodosis: Stability and Antibacterial Assay - Siti Hajar Musa; Nurul Izzah Ismail; Faizan Naeem Razali (Asian Journal of Medicine & Health Sciences, 2024)
The current marketed product of antiperspirant could temporarily block the production of excessive sweat in hyperhidrosis patients. The sweat leads to the growth of bacteria, especially in the foot area. Therefore, the chemical compound in bergamot essential oil which is linalool, able to provide antibacterial properties to the emulsion. In this study, the formulation of antiperspirant lotion containing bergamot essential oil as an antibacterial agent has been formulated and optimized at different content of oil, surfactant and aluminium chloride. The formulated emulsion has then been evaluated based on its stability and antibacterial activity. The formulation consisting of 25% aluminium chloride, 3% bergamot essential oil, 6% Tween 80, and 0.5% Phenonip (F1) was selected as the most optimum formulation. It demonstrated good stability in the overtime stability analysis, with no phase separation, no precipitation, no colour changes, and only an insignificant decrease in pH at various storage temperatures (4, 25 and 34°C). In contrast, the other formulated emulsions (F2 to F8), were found to be unstable at high-temperature storage (34°C). The stability of the emulsions was further confirmed by the positive results obtained from the accelerated and freeze-thaw stability analyses. Disk diffusion analysis indicated that the formulated emulsion with a high content of bergamot essential oil highly inhibits the growth of Gram-positive bacteria. However, the use of bergamot essential alone failed to inhibit the growth of Gram-negative bacteria due to the presence of lipopolysaccharide in the bacteria cell wall, which blocks the permeation of antibacterial agents. The newly optimized antiperspirant emulsion could overcome the problem of excessive production of sweat as well as inhibit the growth of bacteria that cause foot odour.